Collaborative praxis learning to empower rural area: an action research - Aziz, Abdul; Barizi, Ahmad; Syuhadak, Syuhadak; Prihadi, Kususanto Ditto; Hamim, Hamim; khayati, Eliya Nur; Mustofa, Syaiful (Institute of Advanced Engineering and Science, 2025)
The emergence of collaborative learning praxis among adult learners has gained prominence, fostering lifelong practical learning. This approach empowers adults to define their learning goals based on interests and needs, facilitating contextual information sharing, knowledge acquisition, and skill enhancement. Such an approach promotes innovation and creativity, strengthening market competitiveness. This study focuses on collaborative learning’s impact in the village of Sukodono, East Java, Indonesia, post-COVID-19. Collaborative learning facilitated skill development, innovation, and market influence. Action research was employed to restore economic well-being. Themes of healthy environment preservation, community self-help, and market power were explored. The villagers’ adoption of biogas technology, digital platforms for product promotion, and focus on high-demand products showcased the efficacy of collaborative learning. This praxis enhances economic conditions and knowledge acquisition, enabling sustainable community development. Further quantitative studies are recommended to assess long-term impacts.